Numerical and experimental analysis of time-dependent load transfer in reinforced concrete columns - Kataoka,L. T. (2014)
A study was conducted to assess the influence of the steel reinforcement ratio in concrete columns on their properties of creep and shrinkage. Experimental tests and three-dimensional finite element-based simulations of the experimental curves from plain concrete cylinders and plain concrete columns derived by curve fitting were performed using the ACI 209 model available in DIANA 9.3. Columns with longitudinal reinforcement ratios of 0%, 1.4% and 2.8%, loaded to 30% and 40% of their 7-day compressive strength, were investigated. The results indicated that numerical simulation does not predict experimental data for a long period. However, simulations fitted with experimental curves derived from plain concrete columns presented values close to those of experimental data for 91 days.